Zu einem geistlich stilisierten Historien-Gemälde in der franziskanischen Wallfahrtskirche zu Nazarje - Kretzenbacher, Leopold (Traditiones (Ljubljana), 1999)
The author writes about two pictorial documents depicting 23 Franciscans who at the end of the 16th century were crucified and died a martyr's death in Nagasaki, Japan. Both pictures originated independently from each other; the first is a stylized oil painting from the Nazarje Franciscan pilgrimage church, the second a realistic lithograph which had been done from a drawing by an unknown author and printed in Innsbruck, Austria
Keywords: art of painting; slikarstvo; cerkvena umetnost; Slovenia; Slovenija